Comparison of hand hygiene antimicrobial efficacy: Melaleuca alternifolia essential oil versus triclosan - Juliana Rizzo Gnatta; Flávia Morais Gomes Pinto; Camila Quartim de Moraes Bruna; Rafael Queiroz de Souza; Kazuko Uchikawa Graziano; Maria Julia Paes da Silva (Universidade de São Paulo, 2013)
OBJECTIVE: this study aimed to evaluate the efficacy of hand hygiene performed with two different soap formulations: 0.3% Melaleuca alternifolia essential oil versus 0.5% triclosan, and to compare them with two reference hygiene procedures: the official methodology procedure (soft soap) versus the draft version of the procedure (soft soap + propan-2-ol). METHOD: using the European EN 1499 method, logarithmic reduction factors were determined for the number of colony forming units of Escherichia coli K12 before and after hand hygiene of 15 volunteer subjects, and compared using the one-tailed Wilcoxon test. RESULTS: referring to the soft soap, there was no difference between the performance of soap with 0.3% M. alternifolia and soap containing 0.5% triclosan. The soft soap + propan-2-ol proved to be more effective than the other hand hygiene procedures. CONCLUSION: studies to verify the therapeutic efficacy of essential oil in hand hygiene can improve adherence to this practice.